Peluang Dan Ancaman Perdagangan Produk Perkebunan Kopi Dan Kebijakan Untuk Mengatasinya: Studi Kasus Indonesia dengan Malaysia - Eka Lidianti; Daspar; Dian Ramadhani; Milawati Dewi; Lulu Dwi Alfiana (CV. ITTC INDONESIA, 2024)
The purpose of this research is to describe the opportunities and risks of free trade between Indonesia and Malaysia in the coffee plantation sector and identify strategies to optimize the potential of this market in the future. This analysis focuses on coffee products which are an important commodity for ASEAN member countries such as Indonesia and Malaysia. Indonesia is the largest coffee producing country in the world, and exporting coffee to Malaysia is fraught with various problems, including problems with the quality of the coffee being exported, complicated regulations and bureaucracy, as well as competition with other producing countries such as Vietnam which faces intense competition. Challenge. To overcome these problems, it is necessary to strengthen supervision of the quality of exported coffee, improve regulations and bureaucracy, and strengthen the promotion of Indonesian coffee on the international market. What is also important is cooperation with other coffee producing countries, training to improve coffee quality, and processing innovation without eliminating traditional elements. Through this analysis, it is hoped that effective strategies can be found to make maximum use of existing opportunities and overcome challenges arising from regional competition. This research will also provide an important contribution to policy makers and industry players in formulating appropriate policies and strategies to support the growth of Indonesian coffee exports in the ASEAN market, especially Malaysia.